Tingkat Kemandirian Pasien Dengan Gangguan Mobilitas Fisik Dengan Berbagai Macam Penyakit - Lisdiana, Renna; Rofi'i, Muhamad (Holistic Nursing and Health Science, 2024)
In Indonesia, 22.5 million people experience disabilities with the highest incidence occurring in those aged 60 years and over (elderly). Meanwhile, the most common impairment or limitation of function experienced by persons with disabilities in Indonesia is impaired walking (immobility). This mobility impairment can affect a person's independence in fulfilling their daily activities.This study aims to determine the level of independence of activity of daily living (ADL) in patients who experience impaired physical mobility. This research is quantitative research with a descriptive survey design. The sampling technique used purposive sampling technique with a total sample of 102 patients who experienced impaired physical mobility aged ≥ 60 years and domiciled in the Sukra Health Center work area. Measurement of ADL independence using the Katz Index questionnaire, which has been back translated and tested for construct validity with a calculated r value of 0.580-0.740 > r table 0.361 which means it is valid. Data were analyzed univariately and cross-tabulated. The results showed that the majority of patients with impaired physical mobility experienced total dependence in performing ADL (23.5%). Total dependence was more experienced by patients aged > 90 years (24.7%), female (26.1%), suffered a stroke (42.6%), lived with family (27.1%), usually assisted by other people (nurses/neighbors/helpers) (50%), and had been hospitalized less than 1 year ago (35%). Patients with impaired physical mobility are expected to be able to fulfill all activities daily living either independently or with the help of others.